Cognitive Complaints in Motor Functional Neurological (Conversion) Disorders: A Focused Review and Clinical Perspective. Issue 2 (June 2020) - Alluri, Priyanka R.; Solit, Juliet; Leveroni, Catherine L.; Goldberg, Katherine; Vehar, Julia V.; Pollak, Lauren E.; Colvin, Mary K.; Perez, David L.
Abstract : Functional neurological (conversion) disorder (FND) is a neuropsychiatric condition characterized by sensorimotor symptoms exhibiting features incompatible with other neurologic diseases. Individuals with motor FND (mFND) typically present with limb weakness, nonepileptic seizures, and/or abnormal movements. However, this population also frequently reports clouded thinking, inattention, and memory difficulties. Cognitive complaints in individuals with mFND are important to evaluate as they may negatively impact quality of life and impede treatment engagement. We provide a narrative review of the neuropsychological testing literature detailing neurocognitive profiles of individuals with mFND. We also present three illustrative clinical cases at the intersection of mFND and cognitive concerns. Several studies and our case examples highlight that generally normal cognitive performance can be observed concurrently with subjective cognitive complaints in some individuals with mFND; this mismatch may be a possible "rule-in" sign of functional cognitive symptoms. Other studies have reported impairments in attention, memory, language, visuospatial, and executive functioning in individuals with mFND. These impairments could be related to medical-psychiatric comorbidities, psychotropic medication side effects, and intrinsic disease mechanisms. When evaluating individuals with mFND and their cognitive complaints, clinicians can use performance validity test and psychopathology findings to help them interpret the neuropsychological test results. Perceptual mismatches between intact objective cognitive performance and subjective cognitive complaints may reflect a negative attentional bias for cognitive abilities that can be targeted with cognitive retraining and cognitive behavioral therapy. Neuropsychological evaluations may provide a useful adjunctive tool clinicians can use to help assess individuals with mFND and cognitive concerns. Abstract : Supplemental Digital Content is available in the text.